2021
DOI: 10.1136/ijgc-2020-002239
|View full text |Cite
|
Sign up to set email alerts
|

Phase II consolidation trial with anti-Lewis-Y monoclonal antibody (hu3S193) in platinum-sensitive ovarian cancer after a second remission

Abstract: ObjectiveTo investigate the efficacy and safety of hu3S193, a humanized anti-Lewis-Y monoclonal antibody, as a consolidation strategy in patients with platinum-sensitive recurrent epithelial ovarian cancer who achieved a second complete response after salvage platinum-doublet chemotherapy.MethodsThis single-arm phase II study accrued patients with recurrent epithelial ovarian cancer with Lewis-Y expression by immunohistochemistry who had achieved a second complete response after five to eight cycles of platinu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Then, the humanized version hu3S193 was constructed, demonstrating potent immune effector function, with higher ADCC and CDC than its murine counterpart [260]. In clinical studies, it demonstrated itself to be safe, with a strong ability to target tumors, justifying further investigation [57,261] (NCT00084799). However, in a phase II study in gynecological cancers (NCT00617773), the clinical benefit of hu3S193 was modest [58].…”
Section: Lewis Antigensmentioning
confidence: 99%
“…Then, the humanized version hu3S193 was constructed, demonstrating potent immune effector function, with higher ADCC and CDC than its murine counterpart [260]. In clinical studies, it demonstrated itself to be safe, with a strong ability to target tumors, justifying further investigation [57,261] (NCT00084799). However, in a phase II study in gynecological cancers (NCT00617773), the clinical benefit of hu3S193 was modest [58].…”
Section: Lewis Antigensmentioning
confidence: 99%
“…This suggested that the drug is expected to be a part of combined immunotherapy and chemotherapy. However, a phase II trial with hu3S193 for the treatment of ovarian, it did not show sufficient activity and with some treatment‐related adverse events such as fatigue, nausea and vomiting 66,67 . More data are needed to investigate the efficacy and safety of hu3S193.…”
Section: The Role Of Abo(h) and Lewis Blood Group In Diseases Treatmentmentioning
confidence: 99%
“…All these studies suggested that Lewis Y was a promising target for the therapy of epithelial cancers including ovarian, breast, and gastric cancers. Lewis Y has been evaluated as a target in several clinical trials using monoclonal antibody (mAb), antibody-drug conjugate (ADC), and chimeric antigen receptor T-Cell immunotherapy (CAR-T); however, a limited clinical benefit has been achieved so far from these trials [30,31].…”
Section: Introductionmentioning
confidence: 99%